The role of fixed asset accounting in improving company operations at Ud Tiga Berlian - Silifusti, Intan; Adil Siswanto (YAYASAN MITRA PERSADA NUSANTARA, 2025)
Fixed assets are assets that are acquired and used for company operations not for sale and have a useful life of more than one year. Basically, each company uses a different approach in managing its assets, as is the case with UD Tiga Berlian which has fulfilled the classification of PSAK No. 16. The research focus in this study is 1) how is the role of fixed asset accounting in improving UD Tiga Berlian company operations? 2) whether fixed assets can improve the company's operations UD Tiga Berlian? The objectives to be achieved in this study are 1) to determine the role of fixed asset accounting in improving the operations of the company UD Tiga Berlian 2) to determine whether fixed assets can improve the operations of the company UD Tiga Berlian. This research uses a qualitative approach with descriptive research type. Using the type of field research with data collection techniques taken from the results of observations, interviews, and documentation by going directly to the field and interviewing related parties. The results of this study are 1) Fixed asset accounting at UD Tiga Berlian has a significant role in supporting company operations. This is because the application of fixed assets is carried out in accordance with PSAK No. 16, making it easier for companies to keep accurate records, transparency, and make better decisions. 2) Fixed assets that are managed properly as well as in terms of recording or maintenance can help companies minimize the occurrence of damage or loss of existing assets and can extend their useful life.